METODE IJTIHAD T. M. HASBI ASH-SHIDDIEQY SEBAGAI PRODUK PEMIKIRAN HUKUM ISLAM - Hasbi, Muhammad (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: This paper will examine the method of ijtihad Hasbi Ash-Shiddieqy in giving birth to Islamic legal thought products. Ijma ', qiyas, Istihsan, maslahah al-mursalah, and' urf is a method or means in producing law as a product of Islamic legal thought. The five principles that enable Islamic law to develop in keeping with the times, namely; first; principle of ijma '. Second, the principle of qiyas. Third; maslahah al-mursalah. Fourth; maintenance 'urf. Fifth; changing law with changing times.